2006
DOI: 10.1194/jlr.m500203-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

PPARα activation increases triglyceride mass and adipose differentiation-related protein in hepatocytes

Abstract: Adipose differentiation-related protein (ADRP) is a lipid droplet-associated protein that is expressed in various tissues. In mice treated with the peroxisome proliferatoractivated receptor a (PPARa) agonist Wy14,643 (Wy), hepatic mRNA and protein levels of ADRP as well as hepatic triglyceride content increased. Also in primary mouse hepatocytes, Wy increased ADRP expression and intracellular triglyceride mass. The triglyceride mass increased in spite of unchanged triglyceride biosynthesis and increased palmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
60
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 65 publications
10
60
0
3
Order By: Relevance
“…PPARa-mediated transcriptional regulation of ADFP in liver was recently also demonstrated by others (50), which supports our findings.…”
Section: Discussionsupporting
confidence: 82%
“…PPARa-mediated transcriptional regulation of ADFP in liver was recently also demonstrated by others (50), which supports our findings.…”
Section: Discussionsupporting
confidence: 82%
“…In comparison, in the above mentioned study, Fujiwara et al (2003) detected stimulation of PPAR-γ mRNA expression (isoform not specifi ed) in HepG2 cells following 24 h oleate treatment 27 . In a recent study by Edvardsson et al (2006) isolated mouse hepatocytes maintained with 0.5 mmol/l oleate (in the presence of 0.75% albumin and 11 mmol/l glucose) were markedly upregulated PPAR-γ2 mRNA amount, whereas that of PPAR-γ1 mRNA remained unchanged 30 . Species and model variations are likely to be taken into account to un-243 mRNA levels of peroxisome proliferator-activated receptors and their coactivators are aff ected by glucose deprivation and oleate in human hepatoma HepG2 cells derstand the cause of these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the addition of fatty acid to various cells induces ADRP expression and LD formation and that PPAR-RXR heterodimers are involved in mRNA expression of the ADRP gene (19)(20)(21)(22)(23)(24)(25). We tested the effect of fatty acids on the distribution of ADRP using HuH-7 hepatocytes, but we did not observe ADRP distribution in the iLD fractions by…”
Section: Induction Of Adrp-associated Ild Fractions In Huh-7 Human Hementioning
confidence: 99%
“…The expression of Adrp mRNA is induced not only in adipocytes but also in many other types of cells upon lipid accumulation (17)(18)(19)(20)(21). It is reported that peroxisome-proliferator activated protein (PPAR)-retinoid X receptor (RXR) heterodimers are responsible for ADRP transcription, while PPAR ␥ is the major subtype in adipose tissue and the placenta ( 22,23 ), PPAR ␦ is crucial in macrophages ( 19 ), and PPAR ␣ acts in the liver ( 20,24 ).…”
Section: Immunoblot Analysismentioning
confidence: 99%